When Cannabis Use Goes Wrong: Mental Health Side Effects of Cannabis Use That Present to Emergency Services - Crocker, Candice E.; Carter, Alix J. E.; Emsley, Jason G.; Magee, Kirk; Atkinson, Paul; Tibbo, Philip G. (Frontiers in Psychiatry, 2021)
Cannabis use is a modifiable risk factor for the development and exacerbation of mental illness. The strongest evidence of risk is for the development of a psychotic disorder, associated with early and consistent use in youth and young adults. Cannabis-related mental health adverse events precipitating Emergency Department (ED) or Emergency Medical Services presentations can include anxiety, suicidal thoughts, psychotic or attenuated psychotic symptoms, and can account for 25-30% of cannabis-related ED visits. Up to 50% of patients with cannabis-related psychotic symptoms presenting to the ED requiring hospitalization will go on to develop schizophrenia. With the legalization of cannabis in various jurisdiction and the subsequent emerging focus of research in this area, our understanding of who (e.g. age groups, risk factors) are presenting with cannabis-related adverse mental health events in an emergency situation is starting to become clearer. For years we have heard in popular culture that cannabis use is less harmful or no more harmful than alcohol use; however, this does not appear to be the case for everyone. It is evident that these ED presentations should be considered another aspect of potentially harmful outcomes that need to be included in knowledge mobilization. In the absence of a clear understanding of the risk factors for mental health adverse events with cannabis use it can be instructive to examine what characteristics are seen with new presentations of mental illness both in emergency departments (ED) and early intervention services for mental illness. In this narrative review, we will discuss what is currently known about cannabis-related mental illness presentations to the ED, discussing risk variables and outcomes both prior to and after legalization, including our experiences following cannabis legalization in Canada. We will also discuss what is known about cannabis-related ED adverse events based on gender (including transgender individuals) and biological sex. Where possible, we will discuss the differences between the impact of alcohol and cannabis on emergency mental health services to fairly present the magnitude of the problem with the understanding that these two recreational substances may impact different populations of individuals at risk for adverse events.